MINAT BERSEKOLAH MASYARAKAT DESA RANAH SUNGKAI KEC. XIII KOTO KAMPAR KAB. KAMPAR - Putri Clawson; Raudatul Jannah (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2020)
The background of this research problem is the interest in attending the Ranah Sungkai Village community in the XIII Koto District. This research uses a qualitative approach. Qualitative research is research conducted with a background that is reasonable and natural and holistic. Qualitative research seeks to see, examine, and appreciate the problem to be examined as a complex phenomenon that must be examined holistically or thoroughly. Data collection techniques are done by direct observation to the field and in-depth interviews (depth interviews) with informants through documentation. Based on research findings Factors that influence the interest in schooling in the Ranah Sungkai village community XIII Subdistrict Koto Kampar Kampar Regency are the interests in the Ranah Sungkai village community school influenced by the school's relationship with the community that has not been harmoniously established. the economy of the Ranah Sungkai village community that is very difficult or still depends on natural conditions, local culture (peer environment), the distance between residents 'homes and schools is very far away and the parents' lack of understanding of the importance of education. The efforts of the Ranah Sungkai Village community in overcoming the occurrence of school dropouts are raising parents' awareness of the importance of children's education, providing encouragement and assistance to children in learning, conducting supervision and providing motivation to children,